Menakar Efektivitas Hukum tentang Batas Minimal Usia Kawin pada Kantor Urusan Agama (KUA) Kota Jayapura - Burhanuddin; Mifathul Huda; Faisal; Athoillah Islamy (Al Hikmah: Jurnal Studi Keislaman, 2023)
The enactment of new laws related to the minimum age limit to be able to carry out marriages does not always work effectively in various regions in Indonesia. This study intends to identify factors of ineffectiveness of Law No.16 of 2019 concerning the minimum age of marriage at the Office of Religious Affairs (District (South Jayapura District, Abepura and Heram) of Jayapura City in the period 2019-2021. This qualitative study is normative-empirical legal research. Soerjono Soekanto's theory of legal effectiveness became the theory of subject matter analysis. Data collection techniques through observation, interviews and documentation. The results of the study conclude that the lack of effectiveness of the implementation of the new law on the marriage age limit in Jayapura City is caused by a variety of factors that cause there are still many cases of marriage dispensation, such as the lack of knowledge and awareness of public attitudes towards the implementation of the law, the lack of legal culture, and the lack of socialization of legal enforcement. The theoretical implications of this study show that synergy of supporting factors is needed in realizing the effectiveness of the law of the minimum age of marriage, both juridical, sociological and anthropological supporting factors. The limitations of this study have not examined the concrete role of religious (Islamic) leaders in various districts of Jayapura in the succession to the effectiveness of the implementation of new laws related to the minimum age of marriage.